The Notion of "Religion" in Nostra Aetate: Said, Unsaid, and Still to Say - Huspeková, Tereza (Verbum Vitae, 2026)
This article examines the understanding of “religion” in Vatican II’s declaration Nostra aetate, arguing that it reflects an intellectual climate characteristic of mid-20th-century theological reflection. The study is divided into three sections. First, it outlines what Nostra aetate explicitly said about non-Christian religions within the broader conciliar teaching, particularly in relation to fulfillment theology, praeparatio evangelica, and semina Verbi. Second, it identifies what remained unsaid—the tacit, implied assumptions about religion in Nostra aetate, which align with phenomenological and historical approaches prevalent among the Council experts. Finally, it considers what there is still to say, exploring how the interpretation of religion may shift if the historical–phenomenological framework is complemented by recent approaches that view religion as a human, evolutionary phenomenon. This third part proposes (1) a theological engagement with such naturalistic accounts of religiosity, (2) an expanded theological reflection that also includes “non-religion,” and (3) an alternative approach to patristic insights into human religiousness. The study is based on the analysis and interpretation of selected themes in Nostra aetate, in dialogue with relevant sources in religious studies. It concludes by stressing the contextual character of the Council’s approach and opening space for further multiperspective inquiry.